Calycosin Suppresses RANKL-Mediated Osteoclastogenesis through Inhibition of MAPKs and NF-κB - Quan, Gui-Hua (Int J Mol Sci, 2015)
Calycosin, an isoflavonoid phytoestrogen, isolated from Radix Astragali, was reported to possess anti-tumor, anti-inflammation, and osteogenic properties, but its impact on osteoclast differentiation remains unclear. In this study, we examined the effects of calycosin on osteoclastogenesis induced by RANKL. The results showed that calycosin significantly inhibited RANKL-induced osteoclast formation from primary bone marrow macrophages (BMMs). Calycosin also dose-dependently suppressed the formation of bone resorption pits by mature osteoclasts. In addition, the expression of osteoclatogenesis-related genes, including cathepsin K (CtsK), tartrate-resistant acid phosphatase (TRAP), and MMP-9, was significantly inhibited by calycosin. Furthermore, the results indicated that calycosin down-regulated the expression levels of NFATc1 and c-Fos through suppressing the activation of NF-κB and MAPKs. Our results indicate that calycosin has an inhibitory role in the bone loss by preventing osteoclast formation, as well as its bone resorptive activity. Therefore, calycosin may be useful as a therapeutic reagent for bone loss-associated diseases.